Non-oriented electrical steel sheet and its manufacturing method

The non-oriented electrical steel sheet with controlled grain sizes and textures through Si, Sn, and N addition, and nitriding, addresses the challenges of high-frequency iron loss and magnetic flux density, improving the efficiency and productivity of electrical equipment.

JP7601881B2Active Publication Date: 2024-12-17CLEANSOLUTION CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022538103
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-17
Publication Date
2024-12-17
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

Existing non-oriented electrical steel sheets face challenges in achieving high magnetic flux density and low iron loss, particularly at high frequencies, due to issues with grain size and texture control, which are exacerbated by the addition of alloying elements like Si and Mn, leading to poor workability and increased production costs.

Method used

A non-oriented electrical steel sheet with controlled crystal grain sizes and textures achieved by adding Si, Sn, and N, with a manufacturing process involving nitriding to create a surface layer with fine grains and a center portion with larger grains, optimized through specific annealing processes.

Benefits of technology

The solution results in a steel sheet with improved magnetic flux density and reduced iron loss across both low and high frequencies, enhancing the efficiency and productivity of electrical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601881000007
    Figure 0007601881000007
  • Figure 0007601881000001
    Figure 0007601881000001
  • Figure 0007601881000002
    Figure 0007601881000002
Patent Text Reader

Abstract

An object of the present invention is to provide a non-oriented electrical steel sheet having improved magnetic properties by appropriately adding Si and Sn and improving the texture through nitriding, and a method for producing the same. [Solution] The non-oriented electrical steel sheet of the present invention contains, by weight, 2.2 to 4.5% Si, 0.5% or less (excluding 0%) Mn, 0.001 to 0.5% Al, 0.07 to 0.25% Sn, and 0.0010 to 0.0090% N, with the remainder consisting of Fe and unavoidable impurities. The steel sheet includes a surface layer portion that exists from the surface toward the inside of the steel sheet, and a center portion that exists within the surface layer portion, the center portion containing N: 0.005% by weight or less, the surface layer portion further containing N by 0.001% by weight or more compared to the center portion, the surface layer portion having an average crystal grain size of 60 μm or less, and the center portion having an average crystal grain size of 70 to 300 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-oriented electrical steel sheet and a manufacturing method thereof, and more particularly to a non-oriented electrical steel sheet having improved magnetic properties by appropriately adding Si and Sn and improving the texture through nitriding, and a manufacturing method thereof. [Background technology]

[0002] Non-oriented electrical steel sheets are used as iron core materials in rotating equipment such as motors and generators, and electrical equipment such as small transformers, and play an important role in determining the energy efficiency of electrical equipment. Representative characteristics of electrical steel sheets include iron loss and magnetic flux density. The lower the iron loss, the higher the magnetic flux density. This is because when an electric field is applied to an iron core to induce a magnetic field, the lower the iron loss, the less energy is lost as heat, and the higher the magnetic flux density, the stronger the magnetic field can be induced with the same energy. In recent electrical equipment, the use of high frequency ranges is increasing for the purpose of high efficiency and miniaturization, and in particular, environmentally friendly drive motors for electric vehicles and the like strongly demand improved magnetic properties in the high frequency range of 400 Hz or higher, and as speeds increase, iron loss at several to several tens of kHz also becomes important. In the case of automotive motors, it is particularly good if both high-frequency and low-frequency iron loss are excellent.

[0003] In order to reduce high frequency iron loss, alloy elements with high resistivity such as Si, Al, Mn, etc. are added, but although this method reduces iron loss, there is a risk of reducing saturation magnetic flux density. Also, if the amount of Si added is too high, workability decreases, making cold rolling difficult and reducing productivity, and the more Al, Mn, etc. are added, the lower the rollability becomes, the higher the hardness becomes, and the lower the workability becomes. Furthermore, in the case of silicon steel sheets with more than 6.5% by weight, the cold workability is reduced, making it impossible to produce them by ordinary cold rolling, and methods such as siliconizing must be used. There is also a method of manufacturing the sheets by making them very thin, but the thinner the steel sheet, the higher the production costs become, and even when manufacturing motors, the production costs increase due to the difficulty of the manufacturing process and the increase in the number of layers.

[0004] In order to improve magnetic flux density and core loss, a method of improving the texture has been proposed. A method has been proposed in which the surface of a cold-rolled steel sheet is annealed to cause selective crystal growth of (100) crystal grains, so that the surface of the annealed sheet has a (100)[0vw] crystal orientation. Hereinafter, crystal orientations are represented by Miller indices. Crystal orientations are expressed as {hkl} <uvw>or (hkl)[uvw], where {hkl} is the plane index of the crystal plane parallel to the surface orientation, <uvw>indicates the crystal direction parallel to the rolling direction. h, k, l, u, v, and w are integers. In this technology, the crystal grain size is all larger than the thickness and has a structure that penetrates the thickness. Non-oriented electrical steel sheets are manufactured into complex shapes such as motor cores through punching, so if the grain size becomes too large, the workability becomes very poor.

[0005] Also, a method for forming a {100} plane parallel to the metal plate surface has been presented. The method includes a heat treatment step of heat treating the metal plate at a temperature at which the austenite phase is stable while reducing oxygen in at least one of the internal region and the surface region of the metal plate or isolating the metal plate from external oxygen, and a step of transforming the heat-treated metal plate into a ferrite phase. This method requires vacuum heat treatment, which is difficult to carry out industrially because it requires isolation from oxygen from the outside, and the heat treatment takes a long time, making it a very difficult process to achieve industrially. However, while iron loss can be expressed as the sum of hysteresis loss, eddy current loss, and anomalous eddy current loss, in the case of high frequency characteristics, the ratio of eddy current loss increases, and methods other than texture control, which are important for hysteresis loss, are required. Factors that have a large effect on eddy current loss include resistivity, sheet thickness, and grain size. The resistivity and sheet thickness of steel sheet are as described above. Regarding grain size, when the grain size decreases, the eddy current loss decreases. However, a decrease in grain size actually increases hysteresis loss. This is why the optimal grain size is set.

[0006] Considering the iron loss according to frequency, it is generally known that the optimum grain size of steel sheet for high frequency motors is smaller than the optimum grain size for general low frequencies. Furthermore, as the frequency increases, eddy currents are mainly formed on the surface due to the skin depth effect, making it necessary to refine the surface crystal grains or increase the surface resistivity. When high-frequency current flows, the current is concentrated on the surface of the conductor, and the depth at which 1 / e (36.5%) of the surface current flows is called the skin depth. δ=(2ρ / μω) 1 / 2 ~503.3*(ρ / μrf) 1 / 2 δ: skin depth [m], ρ: electrical resistivity [Ωm], μr: relative permeability, f: frequency In the case of silicon-containing iron, the skin depth is approximately 200 μm at 50 Hz, but becomes thinner to about 100 μm at 400 Hz and 35 μm at 2000 Hz. Therefore, by making the surface grains smaller, eddy current loss is reduced, which can suppress the formation of eddy currents on the surface at high frequencies and improve high-frequency iron loss.In addition, by making the center grains larger, hysteresis loss is reduced, which can reduce iron loss, and in particular low-frequency iron loss is improved or at least deterioration is prevented.

[0007] As a method for improving high-frequency characteristics, a method is known in which a nitride- and / or internal oxide-containing layer is formed in the surface layer of a steel sheet, in which the average particle size of the nitrides and / or internal oxides from the surface layer of the steel sheet and the area ratio in the sheet thickness cross section are regulated to a predetermined range, and the area ratio in the sheet thickness cross section of the nitrides and internal oxides present in regions other than the nitride- and / or internal oxide-containing layer and the average crystal grain diameter D of the steel sheet are regulated to a predetermined range. However, in this method, it has been reported that the formation state of the nitrides and internal oxides and their average particle size are controlled by adjusting the annealing temperature, annealing time, and annealing atmosphere (N2 concentration, dew point, etc.). In particular, the particle diameter of the internal oxides and nitrides was controlled mainly by changing the annealing temperature and annealing time, the formation depth of the internal oxide-containing layer and nitride-containing layer was controlled mainly by changing the annealing time and annealing atmosphere, and the area ratio of the internal oxides and nitrides in the sheet thickness cross section was controlled mainly by changing the annealing atmosphere and annealing temperature. When using coarse oxides and nitrides like these, they must be contained in very large amounts in order to control the crystal grain size, and it is difficult to control them efficiently in a short period of time. Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a non-oriented electrical steel sheet and a manufacturing method thereof. More specifically, the present invention provides a non-oriented electrical steel sheet and a manufacturing method thereof in which Si and Sn are appropriately added and texture is improved through nitriding, thereby improving magnetic properties. [Means for solving the problem]

[0009] The non-oriented electrical steel sheet of the present invention contains, by weight, 2.2-4.5% Si, 0.5% or less (excluding 0%) Mn, 0.001-0.5% Al, 0.07-0.25% Sn, and 0.0010-0.0090% N, with the balance being Fe and unavoidable impurities. The steel sheet includes a surface layer portion existing from the surface toward the inside of the steel sheet, and a center portion existing inside the surface layer portion, the center portion contains 0.005% by weight or less of N, the surface layer portion further contains 0.001% by weight or more of N compared to the center portion, the surface layer portion has an average crystal grain size of 60 μm or less, and the center portion has an average crystal grain size of 70 to 300 μm. More specifically, the center portion has an average crystal grain size of 70 to 130 μm.

[0010] The non-oriented electrical steel sheet of the present invention may further contain one or more of C: 0.005% by weight or less and S: 0.003% by weight or less. The non-oriented electrical steel sheet of the present invention may further contain one or more of Sb: 0.2% by weight or less and P: 0.1% by weight or less.

[0011] The non-oriented electrical steel sheet of the present invention may further contain one or more of Cu: 0.015 wt.% or less, Ni: 0.05 wt.% or less, Cr: 0.05 wt.% or less, Zr: 0.01 wt.% or less, Mo: 0.01 wt.% or less, and V: 0.01 wt.% or less. The surface layer portion contains nitrides, and the average particle size of the nitrides may be 10 to 100 nm. The average crystal grain size in the central portion may be at least twice the average crystal grain size in the surface layer portion.

[0012] Among the crystal grains in the central portion, the fraction of crystal grains whose {100} planes form an angle of 15° or less with the rolling surface may be 30% or more. Among the central grains, {001} <012> The fraction of grains having orientations that deviate by 15° or less may be 20% or more. The center is {001} when shown by ODF (orientation distribution function). <012> The intensity of the orientation can be seven times or more than random. Among the crystal grains in the central portion, the fraction of crystal grains whose {111} planes form an angle of 15° or less with the rolling surface may be 25% or less.

[0013] The non-oriented electrical steel sheet of the present invention is B 50 / B s ≧0.84 can be satisfied. (B 50 indicates the magnitude (Tesla) of the magnetic flux density induced when a magnetic field of 5000A / m is applied, and B S indicates the saturation magnetic flux density value (Tesla). The non-oriented electrical steel sheet of the present invention is W 15 / 50 is 1.94W / kg or less, and W 10 / 1000 can be 43 W / kg or less. (W 15 / 50 indicates the average loss in the rolling direction and perpendicular to the rolling direction when a magnetic flux density of 1.5 Tesla is induced at a frequency of 50 Hz, and W 10 / 1000 indicates the average loss in the rolling direction and perpendicular to the rolling direction when a magnetic flux density of 1.0 Tesla is induced at a frequency of 1000 Hz.)

[0014] The method for producing a non-oriented electrical steel sheet of the present invention includes the steps of hot rolling a slab containing, by weight, 2.2-4.5% Si, 0.5% or less (excluding 0%) Mn, 0.001-0.5% Al, 0.07-0.25% Sn, 0.005% or less (excluding 0%) N, with the balance being Fe and unavoidable impurities, to produce a hot-rolled sheet, cold rolling the hot-rolled sheet to produce a cold-rolled sheet, and final annealing the cold-rolled sheet. The final annealing step includes a nitriding annealing step and a grain growth annealing step, and when the cold-rolled sheet is heated to perform the nitriding annealing, the heating rate from 300°C to the nitriding annealing temperature is 30°C / sec or more, the amount of nitride in the nitriding annealing step is 10-80 wt ppm, and the temperature in the grain growth annealing step is 960-1200°C. In the stage of producing the cold rolled sheet, the final rolling reduction may be 60 to 88%. The temperature of the nitriding annealing step may be 700 to 850°C. The nitriding annealing step may be performed in an atmosphere containing ammonia, nitrogen and hydrogen. Effect of the Invention

[0015] According to the present invention, by controlling the crystal grain size by controlling the precipitates in the thickness direction differently through the addition of Si, Mn, Al and Sn content among the alloy elements to the steel and nitriding, it is possible to produce a non-oriented electrical steel sheet that is excellent in both high-frequency iron loss and low-frequency iron loss. In addition, nitriding and surface grain refinement make it possible to produce a non-oriented electrical steel sheet with excellent strength. [Brief description of the drawings]

[0016] [Figure 1] 1 shows a schematic diagram of a cross section of a non-oriented electrical steel sheet according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, the first part, component, region, layer or section described below may be referred to as a second part, component, region, layer or section without departing from the scope of the present invention. The terminology used herein is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the text clearly indicates otherwise. The meaning of "comprising" as used in the specification embodies certain features, regions, integers, steps, operations, elements and / or components and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements and / or components. When an element is referred to as being "on" another element, it means that it is immediately on top of the other element, or there may be other elements between them. In contrast, when an element is referred to as being "directly on" another element, there are no other elements between them.

[0018] Moreover, unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight. In an embodiment of the present invention, the term "additionally contain an additional element" means that the additional element is included in place of the remaining iron (Fe) by an amount corresponding to the additional element.

[0019] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted to have a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted in an ideal or very formal sense unless defined. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art will be able to easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.

[0020] A non-oriented electrical steel sheet according to one embodiment of the present invention contains, by weight, 2.2-4.5% Si, 0.5% or less (excluding 0%) Mn, 0.001-0.5% Al, 0.07-0.25% Sn, and 0.0010-0.0090% N, with the remainder being Fe and unavoidable impurities. The reasons for limiting the components of the non-oriented electrical steel sheet will be explained below.

[0021] Si:2.20~4.50wt% Silicon (Si) is an element that increases resistivity and reduces eddy current loss during core loss. If too little Si is added, it may be difficult to obtain low core loss characteristics. On the other hand, if too much Si is added, plate breakage may occur. Therefore, the Si content may be 2.5 to 4.0 wt %. More specifically, the Si content may be 2.70 to 4.80 wt %. Even more specifically, the Si content may be 2.90 to 3.50 wt %.

[0022] Mn: 0.50% by weight or less As the amount of manganese (Mn) added increases, the saturation magnetic flux density decreases. In addition, since Mn is an austenite forming element in the present invention, it is preferable that Mn is not added in order to satisfy the range in which solid phase transformation does not occur. However, when the Si content is high, the amount of Mn that does not form austenite may increase even if the manganese content is high. Since Mn has the effect of increasing the resistivity and can improve the core loss, it is preferable to add a portion of Mn, and the amount of Mn can be 0.5% or less within the range in which austenite is not formed, excluding 0%. More specifically, Mn can be contained at 0.01 to 0.50 wt%.

[0023] Al:0.001~0.500wt% Aluminum (Al) is an element that increases resistivity and reduces eddy current loss, but the texture changes as the Al content increases. If too little Al is added, it reacts with a very small amount of N to form very fine AlN, which can deteriorate the magnetic property. On the other hand, if too much Al is added, Al oxides are distributed on the surface, and Al nitrides have a negative effect on the magnetic property and can also deteriorate the coating adhesion. Therefore, the Al content can be 0.001 to 0.500 wt %. More specifically, the Al content can be 0.010 to 0.400 wt %.

[0024] Sn:0.07~0.25wt% Tin (Sn) is a grain segregation element, and is added to suppress the diffusion of nitrogen through the grain system, suppress the formation of {111} and {112} textures that are harmful to magnetism, and increase {100} and {110} textures that are favorable to magnetism, thereby improving magnetic properties. If too little Sn is added, the above-mentioned effects cannot be fully obtained. If too much Sn is added, grain growth is suppressed, magnetic properties are reduced, and rollability may be deteriorated. Therefore, Sn may be contained in an amount of 0.070 to 0.250 wt %. More specifically, Sn may be contained in an amount of 0.100 to 0.230 wt %. However, since Sn has an effect on the diffusion of nitrogen, in one embodiment of the present invention, in order to reduce the nitriding interference caused by the segregation of Sn, nitriding may be performed first at a temperature before the segregation of Sn, and then grain growth annealing may be performed.

[0025] N:0.0010~0.0090wt% Nitrogen (N) is preferably not added to the slab since it forms fine and long AlN precipitates and inhibits grain growth, but taking into consideration the amount that is inevitably added during the steelmaking process, the slab may contain 0.005 wt% or less. More specifically, the slab may contain 0.003 wt% or less. Even more specifically, the slab may contain 0.002 wt% or less. As will be described later in relation to the manufacturing process, in one embodiment of the present invention, the N content is increased through a nitriding process. Therefore, the final manufactured non-oriented electrical steel sheet may contain 0.0010 to 0.0090 wt% of N. As described below, in one embodiment of the present invention, the N content of the surface layer and the center portion may be different from each other, and the above-mentioned N content means an average value for the entire steel sheet. The non-oriented electrical steel sheet according to an embodiment of the present invention may further include one or more of C: 0.005% by weight or less and S: 0.003% by weight or less.

[0026] C: 0.005% by weight or less Carbon (C) combines with Ti, Nb, etc. to form carbides, which weakens the magnetism, and when used as a final electrical product after processing, increases core loss due to magnetic aging, reducing the efficiency of the electrical device, so it may be contained in an amount of 0.005% by weight or less, more specifically, 0.003% by weight or less.

[0027] S: 0.003% by weight or less Sulfur (S) forms fine precipitates, MnS and CuS, which inhibit grain growth and deteriorate magnetic properties, so the amount added can be as small as possible. Therefore, the upper limit can be limited to 0.003% by weight. More specifically, it can be contained in an amount of 0.002% by weight or less.

[0028] The non-oriented electrical steel sheet according to an embodiment of the present invention may further include one or more of Sb: 0.2 wt % or less and P: 0.1 wt % or less. Sb and P have the effect of improving the texture together with Sn described above, and can be additionally added within the above-mentioned range.

[0029] The non-oriented electrical steel sheet according to one embodiment of the present invention may further include one or more of Cu: 0.015 wt.% or less, Ni: 0.05 wt.% or less, Cr: 0.05 wt.% or less, Zr: 0.01 wt.% or less, Mo: 0.01 wt.% or less, and V: 0.01 wt.% or less. In the case of Cu, Ni, and Cr, they react with impurity elements to form fine sulfides, carbides, and nitrides, which have a detrimental effect on magnetic properties, so their contents are limited to Cu: 0.015% by weight or less, Ni: 0.05% by weight or less, and Cr: 0.05% by weight or less. Also, Zr, Mo, V, and other elements are strong carbonitride-forming elements, so it is preferable to avoid adding them as much as possible, and the contents are set to Zr: 0.01% by weight or less, Mo: 0.01% by weight or less, and V: 0.01% by weight or less.

[0030] The balance is composed of Fe and unavoidable impurities. The unavoidable impurities are impurities that are mixed in during the steelmaking stage and the manufacturing process of the grain-oriented electrical steel sheet, and are widely known in the art, so a detailed description will be omitted. In one embodiment of the present invention, the addition of elements other than the alloy components described above is not excluded, and various elements may be included within a range that does not harm the technical idea of ​​the present invention. When an additional element is further included, it is included in place of the balance Fe. Examples of unavoidable impurities include B, Mg, etc., and B should be controlled to 0.002 wt % or less and Mg should be controlled to 0.005 wt % or less.

[0031] FIG. 1 shows a schematic cross-sectional view of a non-oriented electrical steel sheet according to an embodiment of the present invention. As shown in FIG. 1, a non-oriented electrical steel sheet 100 according to an embodiment of the present invention includes a surface layer portion 20 existing from the surface of the steel sheet toward the inside, and a central portion 10 existing inside the surface layer portion 20.

[0032] In one embodiment of the present invention, the nitrogen content is made different between the central portion 10 and the surface layer 20 by nitriding, and the nitrides are concentrated in the surface layer 20, which can prevent deterioration of low-frequency iron loss. At the same time, the crystal grain size of the surface layer 20 is refined by the nitrides in the surface layer 20, which can improve high-frequency iron loss. In addition, the texture is improved, and the magnetic flux density can also be improved. The surface layer portion 20 is present at a thickness of 10 to 20% of the total thickness of the steel plate. The surface layer portion 20 can be present on both sides of the steel plate, so that the central portion 10 is present at a thickness of 60 to 80% of the total thickness of the steel plate. More specifically, the surface layer portion 20 can be present at a thickness of 15% of the total thickness of the steel plate.

[0033] In one embodiment of the present invention, the nitrogen content is different between the center portion 10 and the surface layer portion 20 by nitriding. Specifically, the center portion 10 may contain 0.005 wt% or less of N. This is the same as the N content in the slab, which means that nitrogen does not substantially penetrate to the center portion 10 during the nitriding process. The surface layer 20 contains more nitrogen by 0.0010 wt % or more than the nitrogen content of the central portion 10. By making the nitrogen content different in this manner, nitrides can be concentrated in the surface layer 20. A gradient of the nitrogen content can exist in the thickness direction in the surface layer 20 and the central portion 10, and the above-mentioned nitrogen range means an average over the entire thickness. As described above, the entire electrical steel sheet 100 may contain nitrogen in an amount of 0.0010 to 0.0090 wt %. As described above, by intensive nitridation of the surface layer 20, nitrides may be precipitated in the surface layer 20. Specifically, the average particle size of the nitrides may be 10 to 100 nm. The nitrides may be (Al, Si)N, (Al, Si, Mn)N, or AlN.

[0034] The crystal grain size of the surface layer 20 is refined by the nitrides in the surface layer 20, but the crystal grains in the central portion 10 are not refined, and the average crystal grain sizes thereof may differ from each other. Specifically, the surface layer 20 has an average crystal grain size of 60 μm or less, and the central portion 10 has an average crystal grain size of 70 to 300 μm. By controlling the crystal grain size to be different from each other in this way, it is possible to improve low-frequency iron loss and high-frequency iron loss. If the annealing temperature is excessively high and abnormal grains grow in the central portion, unintended crystal grains may grow and iron loss may deteriorate. Therefore, the central portion crystal grain is controlled to 300 μm or less. More specifically, the central portion may have an average crystal grain size of 70 to 130 μm. More specifically, the surface layer 20 may have an average crystal grain size of 20 to 55 μm, and the central portion 10 may have an average crystal grain size of 70 to 120 μm. The crystal grain size means the diameter of a virtual circle having the same area as the crystal grain. The measurement can be performed based on a plane parallel to the rolling surface (ND surface).

[0035] The average crystal grain size of the central portion 10 may be at least twice the average crystal grain size of the surface portion 20 . On the other hand, the texture of the central portion 10 can be improved, and thus the magnetic flux density can be improved. Of the crystal grains in the central portion 10, the fraction of crystal grains whose {100} planes form an angle of 15° or less with the rolling surface may be 30% or more. In one embodiment of the present invention, this value can be increased to 30% or more by adding Sn and carrying out nitriding treatment. This can lead to a dramatic improvement in magnetic flux density. More specifically, the percentage of crystal grains whose {100} planes form an angle of 15° or less with the rolling surface can be 30 to 50%. Among the 10 grains in the center, {001} <012> The fraction of grains having orientations that deviate by 15° or less may be 20% or more. The central part 10, when shown by ODF (orientation distribution function), is {001} <012> The intensity of the orientation can be seven times or more than random. In this way, <012> The development of the orientation texture can improve the circumferential properties. More specifically, among the grains in the center 10, the {001} <012> The fraction of crystal grains having a misorientation of 15° or less may be 20-40%. Among the crystal grains in the central portion, the fraction of crystal grains whose {111} planes form an angle of 15° or less with the rolling surface may be 25% or less.

[0036] When the RD direction is used as a reference, the best direction for magnetism is <100> direction, then <110> ,lastly <111> is the worst. Non-oriented electrical steel sheets have a surface orientation <100> When the magnetic fields are uniformly arranged, they have ideal magnetic properties, but when the magnetic fields are uniformly arranged in the in-plane direction, <112> If the orientation is strongly developed, the magnetic properties become very poor. Furthermore, in non-oriented electrical steel sheets with a high Si content that do not undergo phase transformation, when the volume fraction of crystal grains in which the {112} plane makes an angle of 15° or less with respect to the rolled surface is taken into consideration, there are even more of these than with the {111} orientation. As these orientations also cause many orientations with poor magnetic properties to exist in the direction of the rolled surface, it is necessary to reduce the fraction of such orientations. More specifically, the fraction of crystal grains in which the {111} plane makes an angle of 15° or less with respect to the rolled surface may be 10-25%.

[0037] In this way, the magnetic properties can be improved by controlling the crystal grain size to be different from each other and improving the texture. The degree of texture formation favorable for magnetic properties due to process improvement can be evaluated by dividing the magnetic flux density by the saturation magnetic flux density value according to the Si content. In other words, even if a high magnetic flux density can be obtained with a low silicon content, the iron loss is very poor, so the degree of texture formation with excellent magnetic properties with low iron loss and high magnetic flux density is B. 50 / B s Specifically, the non-oriented electrical steel sheet according to an embodiment of the present invention has a B 50 / B s ≧0.84 can be satisfied. (B 50 indicates the magnitude (Tesla) of the magnetic flux density induced when a magnetic field of 5000A / m is applied, and B S indicates the saturation magnetic flux density value (Tesla). B s can be calculated as follows: Bs=2.1561-0.0413×[Si]-0.0198×[Mn]-0.0604×[Al] [Si], [Mn], and [Al] indicate the contents (wt%) of Si, Mn, and Al in the steel sheet, respectively.

[0038] The non-oriented electrical steel sheet according to one embodiment of the present invention is W 15 / 50 is 1.94W / kg or less, and W 10 / 1000 can be 43 W / kg or less. (W 15 / 50 indicates the average loss in the rolling direction and perpendicular to the rolling direction when a magnetic flux density of 1.5 Tesla is induced at a frequency of 50 Hz, and W 10 / 1000 indicates the average loss in the rolling direction and perpendicular to the rolling direction when a magnetic flux density of 1.0 Tesla is induced at a frequency of 1000 Hz.)

[0039] A method for producing a non-oriented electrical steel sheet according to one embodiment of the present invention includes the steps of hot rolling a slab containing, by weight, 2.2-4.5% Si, 0.5% or less (excluding 0%) Mn, 0.001-0.5% Al, 0.07-0.25% Sn, 0.005% or less (excluding 0%) N, with the balance being Fe and unavoidable impurities, to produce a hot-rolled sheet, cold rolling the hot-rolled sheet to produce a cold-rolled sheet, and final annealing the cold-rolled sheet. Each step will be explained in detail below.

[0040] First, the slab is hot rolled. The alloy composition of the slab has been described above in relation to the alloy composition of the non-oriented electrical steel sheet, so a duplicated description will be omitted. Since the alloy composition does not substantially change during the manufacturing process of the non-oriented electrical steel sheet, the alloy composition of the non-oriented electrical steel sheet and the slab are substantially the same. Specifically, the slab may contain, by weight, Si: 2.2-4.5%, Mn: 0.5% or less (excluding 0%), Al: 0.001-0.5%, Sn: 0.07-0.25%, and N: 0.005% or less (excluding 0%), with the remainder being Fe and unavoidable impurities. The slab may have components that do not form the austenite phase in the pre-solid state temperature range. Other additional elements have been explained in the alloy components of the non-oriented electrical steel sheet, so duplicate explanations will be omitted.

[0041] The slab can be heated before hot rolling. The heating temperature of the slab is not limited, but the slab can be heated at 1050 to 1200°C. If the slab heating temperature is excessively high, the precipitates such as nitrides, carbides, and sulfides present in the slab will be redissolved and then finely precipitated during hot rolling and annealing, which may inhibit grain growth and reduce magnetic properties.

[0042] Next, the slab is hot rolled to produce a hot rolled sheet. The thickness of the hot rolled sheet may be 2.0 to 2.3 mm. In the step of producing the hot rolled sheet, the finish rolling temperature may be 800° C. or more, specifically, 800 to 1000° C. The hot rolled sheet may be coiled at a temperature of 700° C. or less. After the step of producing the hot-rolled sheet, the method may further include a step of annealing the hot-rolled sheet. At this time, the annealing temperature may be 900 to 1150°C. If the annealing temperature of the hot-rolled sheet is too low, the raw steel may contain an excessive amount of Sn, which may result in less grain growth. If the annealing temperature is too high, surface defects may occur. The annealing of the hot-rolled sheet is performed to increase the orientation favorable for magnetic properties as necessary, and may be omitted. The annealed hot-rolled sheet may be pickled.

[0043] Next, the hot rolled sheet is cold rolled to produce a cold rolled sheet. The cold rolling is final rolling to a thickness of 0.10 mm to 0.35 mm. If necessary, the cold rolling step may include one cold rolling step or two or more cold rolling steps with intermediate annealing in between. In this case, the intermediate annealing temperature may be 850 to 1150°C. The final reduction rate during cold rolling can be adjusted to 60% to 88%. If the cold rolling rate is too low, the Goss orientation will develop, and if it is too high, the {111} <112> Since the orientation is strongly developed, it can be adjusted to the above range. When one cold rolling step is included, the reduction rate of one cold rolling step is the final reduction rate, and when two or more cold rolling steps are included, the reduction rate of the last cold rolling step is the final reduction rate.

[0044] The cold rolled sheet is then final annealed. As described above, in one embodiment of the present invention, the magnetic properties can be improved by introducing a nitriding process. Specifically, the final annealing step includes a nitriding annealing step and a grain growth annealing step. When the cold-rolled sheet is heated to nitriding annealing, the heating rate may be 300°C or more to the nitriding annealing temperature. In order to suppress the formation of {111} and {112} orientations and to grow {100} orientation rather than Goss orientation, the appropriate Sn content, appropriate cold rolling reduction and heating rate are very important. This is because increasing the heating rate suppresses the growth of {111} and {112} orientations and favors the growth of {100} orientation. In addition, the heating rate in the range including 300 to 850°C, which is the temperature at which recovery and recrystallization occur, is particularly important, and at this time, when the heating rate is 30°C / second or more, the growth of such {100} orientation appears. More specifically, it may be 100°C / second or more. The temperature of the nitriding annealing step may be 700 to 850°C. If the nitriding temperature is too high, Sn may segregate or an oxide layer may be formed, which may prevent the nitriding from proceeding well. If the temperature is too low, the amount of diffusion may be too small. More specifically, the temperature may be 750 to 800°C. The nitriding annealing step may be performed in an atmosphere containing ammonia, nitrogen and hydrogen. The amount of nitriding can be increased by 10 to 80 ppm by weight through nitriding annealing. Since the nitriding temperature is low, most of the nitrides are present in the surface layer, but if the amount of nitriding is too large, low frequency iron loss may deteriorate. If the amount of nitriding is too small, the effect of refining the crystal grains in the surface layer may not be achieved. More specifically, the amount of nitriding can be 15 to 50 ppm by weight. The amount of nitriding is calculated based on the thickness of the entire electrical steel sheet 100 including the surface layer 20 and the center portion 10.

[0045] The grain growth annealing step can be performed at 960 to 1200° C. Since the Sn content is high and grain growth is suppressed, the final annealing can be performed within the above range. The grain growth annealing time may be 65 seconds to 900 seconds. If the annealing time is too short, the grain size may become small due to grain segregation caused by the high Sn content, which may hinder grain growth. If the annealing time is too long, continuous annealing may be difficult. In addition, the shorter the annealing time, the more economical it is, so from the viewpoint of improving economic efficiency, the grain growth annealing time may be 65 seconds to 330 seconds. The atmosphere during grain growth annealing preferably contains hydrogen and has an oxidation degree (PH2O / PH2) of 0.015 or less (where PH2 means the partial pressure of hydrogen, and PH2O means the partial pressure of water vapor). Furthermore, the grain growth annealing can be performed in a nitrogen and hydrogen atmosphere, and the hydrogen content can be 51 vol % or more.

[0046] After the final annealing, an insulating coating can be formed. The insulating coating can be made of organic, inorganic, or organic-inorganic composite coatings, and can also be made of other insulating coating agents. The present invention will be described in more detail with reference to the following examples, but these examples are merely for the purpose of illustrating the present invention and are not intended to limit the present invention. EXAMPLES

[0047] A slab was prepared containing, by weight, C: 0.0025%, Mn: 0.07%, Al: 0.028%, Si, 3.4%, S: 0.0015%, N: 0.0005%, and the remainder being Fe and other unavoidable impurities, with the Sn content shown in Table 1. The slab was reheated at 1150°C and then hot rolled to 2.0 mm to produce a hot-rolled steel sheet. The hot-rolled steel sheet was then subjected to hot-rolled sheet annealing at 1100°C for 100 seconds, and then slowly cooled to 750°C and air-cooled. The steel sheet was then pickled and cold-rolled to 0.27 mm. The final annealing was performed by nitriding annealing followed by grain growth annealing, with the nitriding annealing temperature and amount of nitriding being as shown below. The grain growth temperature was also changed as shown in Table 1. The final annealing was performed for grain growth time of 300 seconds to produce the electrical steel sheets. At this time, the heating rate up to the nitriding treatment temperature was as shown in Table 1.

[0048] The magnetic properties of the electromagnetic steel sheets thus manufactured were measured. 2 The size was measured in the rolling direction and transverse direction using a single plate size measuring device, and the average value was calculated. The texture was calculated by EBSD measurement, and the results are shown in Table 2 below. The surface layer is up to 15% of the thickness from both surfaces, and the center is the inner part of the surface layer.

[0049] [Table 1]

[0050] [Table 2]

[0051] As shown in Tables 1 and 2, when the heating rate is kept high and the grain size is controlled to be different between the surface and center through nitriding, it can be confirmed that both low frequency iron loss and high frequency iron loss are improved. It can also be confirmed that the strength is improved. This results in the control of low-frequency iron loss through texture control, prevention of deterioration of low-frequency iron loss through growth of the crystal grain size in the center, and improvement of high-frequency iron loss through reduction of the crystal grain size in the surface layer. The reduction in the crystal grain size in the surface layer and the precipitates due to nitriding can contribute to increased motor efficiency through increased tensile strength.

[0052] On the other hand, it can be seen that comparative materials 1 to 3 are not nitriding annealed, and therefore the crystal grain sizes in the surface layer and center are not appropriately adjusted, resulting in inferior magnetic properties. It can be seen that the comparative material 4 has an excessively slow heating rate, resulting in small crystal grain size in the center and inferior magnetic properties. It can be confirmed that the comparative material 5 has a small amount of nitriding, and therefore has a large crystal grain size in the surface layer, inferior high-frequency iron loss, and inferior strength. It can be seen that the comparative material 6 has an excessively high amount of nitriding, so that the crystal grain size in the center is small and the magnetic property is inferior. It was confirmed that the comparative material 7 had an excessively high crystal growth annealing temperature, which resulted in an excessively large crystal grain size in the center, and thus inferior magnetic properties and strength. do. EXAMPLES

[0053] Slabs were prepared containing, by weight, C: 0.002%, Mn: 0.3%, Al: 0.04%, N: 0.0005%, and the contents of Si and Sn were varied as shown in Table 3, with the remainder being Fe and other unavoidable impurities. The slab was reheated at 1150°C and then hot-rolled to 1.6 mm to produce hot-rolled steel sheets. The hot-rolled steel sheets were annealed at 1100°C for 100 seconds, slowly cooled to 750°C, and then air-cooled. The steel sheets were then pickled and cold-rolled to 0.27 mm. In the final annealing, the following three comparative examples were not nitrided, and the remaining ones were nitrided at 780°C to 30 ppm, and then final annealed at 1150°C for 300 seconds in an atmosphere of 95% hydrogen, 5% nitrogen, and a dew point of -25°C (at this time, the oxidation degree PH20 / PH2 value was 0.00076) to produce electrical steel sheets. At this time, the heating rate from 300°C to 780°C was as shown in Table 3. The adhesion was evaluated by a 15 mmφ bending test. If no peeling occurred, it was indicated as good, and if peeling occurred, it was indicated as poor.

[0054] [Table 3]

[0055] [Table 4]

[0056] As shown in Tables 3 and 4, when the Si and Sn contents are appropriate and the amount of nitriding is appropriate, the {111} orientation decreases and the {100} orientation increases, especially the {100} <012> It can be seen that the value increases and the magnetic flux density is improved. It can be confirmed that Comparative Examples 8, 9, and 10 do not contain an appropriate amount of Si and Sn and are not subjected to nitriding annealing, so that the texture is not improved and the magnetic properties are inferior. It can be confirmed that Comparative Example 11 does not contain an appropriate amount of Sn, the texture is not improved, and the magnetic property is inferior. It can also be confirmed that the adhesiveness is inferior. It can be seen that in Comparative Example 12, the heating rate was too low, so the texture was not improved and the magnetic properties were poor. EXAMPLES

[0057] A slab was prepared containing, by weight, 0.002% C, 3.35% Si, 0.035% Al, 0.13% Sn, 0.3% Mn, 0.001% N, 0.0009% S, 0.007% Cu, and the remainder being Fe and other unavoidable impurities. The slab was reheated at 1150°C and then hot rolled to 2.0 mm to produce a hot-rolled steel sheet. The steel sheet was cold-rolled to the thickness shown in Table 5 below and annealed as a non-cold rolled steel sheet. The annealing conditions were 1100°C, followed by slow cooling to 750°C and air cooling. The steel sheet was then pickled, and cold-rolled to 0.27 mm, and the cold-rolled steel sheet was finally annealed. In the final annealing of the cold-rolled steel sheets, the temperature was raised at a rate of 40°C / s, and nitriding annealing was performed at 780°C with a nitriding amount of 35 ppm, and then grain growth annealing was performed at the temperature in Table 5 for 300 seconds.

[0058] [Table 5]

[0059] [Table 6]

[0060] As shown in Tables 5 and 6, it can be seen that when the grain growth annealing temperature is appropriately adjusted, the {111} orientation decreases, the {100} orientation increases, and the magnetic property is improved. On the other hand, in Comparative Example 13, since the crystal grain growth annealing temperature was too low, the texture was not improved and the magnetic properties were inferior. It can be seen that in Comparative Example 14, the crystal grain growth annealing temperature was too high, so that the texture was not improved and the magnetic properties were poor.

[0061] The present invention is not limited to the embodiments, but can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention belongs should understand that the present invention can be embodied in other specific forms without changing the technical idea or essential features of the present invention. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and are not limiting. [Explanation of symbols]

[0062] 10: Center 20: Surface layer 100: Non-oriented electrical steel sheet< / uvw> < / uvw>

Claims

1. The alloy contains, by weight percent, 2.2-4.5% Si, 0.5% or less Mn (except 0%), 0.001-0.5% Al, 0.07-0.25% Sn, and 0.0010-0.0090% N, with the balance being Fe and unavoidable impurities; The steel sheet includes a surface layer portion existing from the surface of the steel sheet toward the inside, and a center portion existing inside the surface layer portion, The central portion contains N: 0.005% by weight or less, and the surface layer portion further contains N: 0.001% by weight or more compared to the central portion, The surface layer has an average crystal grain size of 60 μm or less, and the center portion has an average crystal grain size of 70 to 300 μm, A non-oriented electrical steel sheet, characterized in that the thickness of the surface layer portion is 10 to 20% of the total thickness of the steel sheet.

2. The non-oriented electrical steel sheet according to claim 1, further comprising at least one of C: 0.005% by weight or less and S: 0.003% by weight or less.

3. 3. The non-oriented electrical steel sheet according to claim 1, further comprising at least one of Sb: 0.2 wt % or less and P: 0.1 wt % or less.

4. 4. The non-oriented electrical steel sheet according to claim 1, further comprising one or more of Cu: 0.015 wt. % or less, Ni: 0.05 wt. % or less, Cr: 0.05 wt. % or less, Zr: 0.01 wt. % or less, Mo: 0.01 wt. % or less, and V: 0.01 wt. % or less.

5. The non-oriented electrical steel sheet according to any one of claims 1 to 4, characterized in that the surface layer portion contains nitrides, and the average grain size of the nitrides is 10 to 100 nm.

6. 6. The non-oriented electrical steel sheet according to claim 1, wherein the average grain size in the central portion is at least twice as large as the average grain size in the surface layer portion.

7. 7. The non-oriented electrical steel sheet according to claim 1, wherein the percentage of crystal grains in the central portion, whose {100} planes form an angle of 15° or less with the rolling surface, is 30% or more.

8. The non-oriented electrical steel sheet according to any one of claims 1 to 7, characterized in that, among the grains in the central portion, a fraction of grains having an orientation that deviates from the {001}<012> orientation by 15° or less is 20% or more.

9. The non-oriented electrical steel sheet according to any one of claims 1 to 8, wherein the intensity of the {001}<012> orientation in the central portion is 7 times or more that of random orientation when expressed in ODF (orientation distribution function).

10. 10. The non-oriented electrical steel sheet according to claim 1 , wherein the percentage of crystal grains in the central portion, whose {111} planes form an angle of 15° or less with respect to the rolling surface, is 25% or less.

11. B 50 / B s 11. The non-oriented electrical steel sheet according to claim 1, wherein the non-oriented electrical steel sheet satisfies .gtoreq.0.

84. (B 50 indicates the magnitude (Tesla) of the magnetic flux density induced when a magnetic field of 5000 A / m is applied, and B S indicates the saturation magnetic flux density value (Tesla).

12. W 15/50 is 1.94 W / kg or less, and W 10/1000 The non-oriented electrical steel sheet according to any one of claims 1 to 11, characterized in that it has a strength of 43 W / kg or less. (W 15/50 indicates the average loss in the rolling direction and perpendicular to the rolling direction when a magnetic flux density of 1.5 Tesla is induced at a frequency of 50 Hz, and W 10/1000 indicates the average loss in the rolling direction and in the direction perpendicular to the rolling direction when a magnetic flux density of 1.0 Tesla is induced at a frequency of 1000 Hz.)

13. A method for producing a non-oriented electrical steel sheet according to any one of claims 1 to 12, comprising the steps of: A step of producing a hot-rolled sheet by hot rolling a slab containing, by weight percent, 2.2 to 4.5% Si, 0.5% or less (excluding 0%) Mn, 0.001 to 0.5% Al, 0.07 to 0.25% Sn, and 0.005% or less (excluding 0%) N, with the balance being Fe and unavoidable impurities; cold rolling the hot rolled sheet to produce a cold rolled sheet; final annealing of the cold rolled sheet; The final annealing step includes a nitriding annealing step and a grain growth annealing step, When the cold-rolled sheet is heated to perform the nitriding annealing, the heating rate from 300° C. to the nitriding annealing temperature is 30° C. / sec or more; In the nitriding annealing step, the amount of nitride is 10 to 80 ppm by weight, The temperature of the grain growth annealing stage is 960 to 1200°C. In the step of producing the cold-rolled sheet, the final rolling reduction is 60 to 88%, The method for manufacturing a non-oriented electrical steel sheet, wherein the nitriding annealing step is performed at a temperature of 700 to 850°C.

14. The method of claim 13, wherein the nitriding annealing is performed in an atmosphere containing ammonia, nitrogen and hydrogen.

Citation Information

Patent Citations

  • Silicon steel sheet for high speed compact motor

    JP2001279402A

  • Non-oriented electrical steel sheet with low core loss in high-frequency region

    JP2005120403A

  • Non-oriented electrical steel sheet

    JP2008031490A

  • Method for producing non-oriented magnetic steel sheet

    JP2013189693A

  • Method of manufacturing nonoriented electromagnetic steel sheet

    JP2014173099A